Menantang Paradigma Misi Kristen yang Bersifat Kognitif-Proposisional dengan Mengembangkan Pengetahuan Historis Misi - Maraike Joanna Belle Bangun (Indonesian Journal of Theology, 2015)
Mission, a basic facet of Christianity, has been deployed in many different ways. One strategy has been by means of violence, rooted as this approach has been in a cognitive-propositional mode of thinking. In this article, I show the importance of maintaining a historical understanding of mission, in order to challenge certain realizations of Christian mission-driven by such a cognitive-propositional paradigm. This article appropriates aspects of George A. Lindbeck’s thought, in order to explain the characteristics of the cognitive-propositional paradigm and its implications for Christian mission.